Germinal tumors of the central nervous system: epidemiological characteristics and survival in children Edgardo Rebagliati Martins-Essalud national hospital, 1999-2017 - Paredes-Guerra, Gloria (2018)
Objective: Describe the clinical and epidemiological characteristics, management and survival. Methods: We describe 9 cases of children with extragonadal germinal tumor, located in the sellar and / or suprasellar area, diagnosed in the National Hospital Edgardo Rebagliati Martins - EsSalud during the period 1999-2017.Objective: Describe the clinical and epidemiological characteristics, management and survival. Methods: We describe 9 cases of children with extragonadal germinal tumor, located in the sellar and / or suprasellar area, diagnosed in the National Hospital Edgardo Rebagliati Martins - EsSalud during the period 1999-2017. Results: The average age of presentation is 8.2 years, predominantly in males (55.6%), the main signs and symptoms are vomiting and headache (100%) followed by diplopia (77.7%). The germinal is the most frequent (77.7%). The survival is 77.7%. Conclusion: Brain germinal tumors are infrequent, are usually located in the sellar area and the etiological diagnosis at the beginning and beginning of a specific chemotherapy and radiotherapy treatment show a better response and avoid a second surgery with high survival.  DOI 10.25176/RFMH.v18.n4.1727